Effect of Creative Educational Videos on Self-Efficacy and Handwashing Knowledge among Schoolchildren - A Karina Ariadni; Siti Saidah Nasution; Nur Afi Darti; Muhammad Amru Baihaqi (Talenta Publisher, 2026)
Handwashing is one of the most effective measures to prevent infectious diseases; however, compliance among school-aged children remains low. Limited knowledge and low self-efficacy in performing proper handwashing techniques often lead to inadequate hygiene practices. This study aimed to evaluate the effectiveness of a creative educational video in improving handwashing self-efficacy and knowledge among elementary school students. A pre-experimental study with a one-group pretest–posttest design was conducted in February 2024 at SDN 104190 Paluh Kurau. The participants consisted of 50 sixth-grade students selected using total sampling. Data were collected using validated and reliable questionnaires to measure self-efficacy and handwashing knowledge. Statistical analysis was performed using paired sample t-tests and correlation tests with SPSS software to assess differences before and after the intervention.The results demonstrated a significant improvement in both self-efficacy and knowledge following the educational video intervention. The proportion of students with high self-efficacy increased from 62% before the intervention to 98% after the intervention. Similarly, the proportion of students with good handwashing knowledge rose from 32% to 88%. The mean self-efficacy score significantly increased from 25.14 ± 2.43 to 36.16 ± 4.60 (p = 0.000), while the mean knowledge score increased from 7.06 ± 1.66 to 9.16 ± 1.27 (p = 0.000). In conclusion, creative educational videos are an effective and affordable method for improving handwashing self-efficacy and knowledge among elementary school children.These findings suggest that video-based health education can be a valuable tool in school health promotion programs. Keyword: Handwashing, Self-Efficacy, Health Education, Schoolchildren, Creative Video